Synergistic Enzybiotic Effect of a Bacteriophage Endolysin and an Engineered Glucose Oxidase Against Listeria - David Talens-Perales; José-Antonio Daròs; Julio Polaina; Julia Marín-Navarro (Biomolecules)
Listeria monocytogenes represents one of the main risks for food safety worldwide. Two enzyme-based antimicrobials (enzybiotics) have been combined in a novel treatment against this pathogenic bacterium, resulting in a powerful synergistic effect. One of the enzymes is an endolysin from Listeria phage vB_LmoS_188 with amidase activity (henceforth A10), and the other is an engineered version of glucose oxidase from Aspergillus niger (GOX). Both enzymes, assayed separately against Listeria innocua, showed antibacterial activity at the appropriate doses. The combination of the two enzybiotics resulted in a synergistic effect with a log reduction in viable cells (log N0/N) of 4, whereas, taken separately, the same dose of A10 and GOX caused only 1.2 and 0.2 log reductions, respectively. Flow cytometry and microscopy analyses revealed that A10 treatment alone induced the aggregation of dead cells. L. monocytogenes showed higher resistance to single treatment with GOX or A10 than L. innocua. However, the synergic combination of A10 and GOX resulted in a high lethality of L. monocytogenes with a log N0/N higher than 5 (below the detection limit in our analysis). Altogether, these results represent a novel efficient and eco-friendly antimicrobial treatment against the most lethal food-borne pathogen.